Trauma Patients' Family Members' Perceptions of Nurses' Caring Behaviors. Issue 5 (September 2015) - Nantz, Sarah; Hines, Annette
<x xml:space="preserve">Abstract</x> A mixed methods study was conducted to identify trauma patients' family members' perceptions of nurses' caring behaviors on a trauma step-down unit at a level I trauma center. Family members completed Caring Behaviors Inventory-Short Form 24 and a qualitative section. Quantitative data were analyzed using descriptive statistics. On a scale of 1 to 6, the mean score for individual items was 5.2 (median = 5.3). Participants considered the nurses' behaviors to be indicative of caring in each of the 4 areas measured—assurance, knowledge/skills, respectfulness, and connectedness. Four themes were identified—technical, nonverbal, personal connections, and addressing comfort.